Pemanfaatan Limbah Hasil Konstruksi Bangunan Sebagai Bahan Utama Dalam Rehabilitasi Terumbu Karang - Setiawan, Sofyan; Anshari, Laode; Lolopayung, Oktafiani; Subhan, .; Risfandi, . (Jurnal Manajemen Sumber Daya Perairan, 2018)
Waste derived from construction may form as concrete slabs, bricks, broken tiles, cast iron and many more. These things can be utilized as materials in coral reef rehabilitation. The purpose of this activity is to make a design of artificial reefs that are relatively cheap, environmentally friendly, easily applied and social acceptable as well as helping the coral reef recovery process in the effort of rehabilitation. The substrate made of hard and solid provided a perfect media for coral transplantation and field for natural recruitment.Â  It is actually two wise steps at the same time, that is utilizing unused goods and improve the condition of the damaged coral reef.Keywords: Utilization, waste, construction, rehabilitation, coral reef